Identification of outcome domains in immune checkpoint inhibitor-induced inflammatory arthritis and polymyalgia rheumatica: a scoping review by the OMERACT irAE working group - Ghosh, Nilasha; Couette, Nina; van Binsbergen, Wouter H.; Weinmann, Sophia C.; Jivanelli, Bridget; Shea, Beverley; Bass, Anne R.; Gente, Karolina; Bingham, Clifton O.; Calabrese, Cassandra; Cappelli, Laura C.; Chan, Karmela Kim; et al. (Seminars in arthritis and rheumatism, 2023)
Introduction - Immune checkpoint inhibitors (ICI), increasingly used cancer therapeutics, can cause off-target inflammatory effects called immune-related adverse events (irAEs), including ICI-induced inflammatory arthritis (ICI-induced IA) and polymyalgia rheumatica (ICI-induced PMR). There are no validated classification criteria or outcome measures for these conditions, and adaptation of treatment recommendations from corresponding rheumatic diseases may not be appropriate. We summarized clinical descriptors of ICI-induced IA and ICI-induced PMR and aggregated domains used for these conditions in order to inform the development of a core set of outcome domains. - Methods - As the initial step of the core domain set generation process, we systemically searched Medline (Pubmed), EMBASE, Cochrane, and CINHL through March 2021 to identify all studies that provide both clinical descriptions and domains relevant to ICI-induced IA and ICI-induced PMR. Domains were mapped to core areas, such as pathophysiological manifestations, life impact, resource use, and longevity/survival, as suggested by the OMERACT 2.1 Filter. - Results - We identified 69 publications, over a third of which utilized non-specific diagnoses of “arthritis,” “arthralgia,” and/or “PMR”. Other publications provided the number, the distribution and/or names of specific joints affected, while others labeled the irAE as the corresponding rheumatic disease, such as rheumatoid arthritis or spondyloarthritis. Most distinct domains mapped to the pathophysiology/manifestations core area (24 domains), such as signs/symptoms (13 domains), labs (6 domains), and imaging (5 domains), with harm domains of adverse effects from irAE treatment and fear of irAE treatment decreasing ICI efficacy. Forty-three publications also referenced irAE treatment and 35 subsequent response, as well as 32 tumor response. - Conclusion - There is considerable heterogeneity in the domains used to clinically characterize ICI-induced IA and ICI-induced PMR. There were several domains mapped to the pathophysiologic manifestations core area, although several publications highlighted domains evenly distributed among the other core areas of life impact, longevity/survival and resource use.
Online verfügbar: 26. Oktober 2022, Artikelversion: 10. November 2022
Gesehen am 03.09.2024